2009
DOI: 10.1186/1750-1326-4-53
|View full text |Cite
|
Sign up to set email alerts
|

ZnT3 mRNA levels are reduced in Alzheimer's disease post-mortem brain

Abstract: BackgroundZnT3 is a membrane Zn2+ transporter that is responsible for concentrating Zn2+ into neuronal presynaptic vesicles. Zn2+ homeostasis in the brain is relevant to Alzheimer's disease (AD) because Zn2+ released during neurotransmission may bind to Aβ peptides, accelerating the assembly of Aβ into oligomers which have been shown to impair synaptic function.ResultsWe quantified ZnT3 mRNA levels in Braak-staged human post mortem (pm) brain tissue from medial temporal gyrus, superior occipital gyrus, superio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 47 publications
(60 reference statements)
1
41
0
Order By: Relevance
“…Our results of decreased ZnT3 in AD are consistent with a decrease in ZnT3 mRNA recently reported (Beyer et al, 2009).…”
Section: Discussionsupporting
confidence: 93%
“…Our results of decreased ZnT3 in AD are consistent with a decrease in ZnT3 mRNA recently reported (Beyer et al, 2009).…”
Section: Discussionsupporting
confidence: 93%
“…For example, ZnT2 is up-regulated in the mammary gland during lactation through the elevation of prolactin, which acts as a transcriptional transactivator (41). As an example of a pertaining pathological state, ZnT3 mRNA levels were shown to be markedly reduced in brain tissue from patients with Alzheimer disease (42). Although women carrying the G87R-ZnT2 mutation did not show other known related symptoms except for low levels of zinc in their breast milk (11,13), based on our current data instigating heterodimerization of ZnT2 with ZnT1, ZnT2 with ZnT3, and ZnT2 with ZnT4, it is possible that the dominant negative effect of the G87R-ZnT2 mutant mediates additional pathologic alterations on other ZnTs that were not described before.…”
Section: Discussionmentioning
confidence: 99%
“…These findings may support the theory that ZnT3 is involved in the formation of senile plaques and cerebral amyloid angiopathy. On the contrary, another study demonstrated that in human post mortem brain tissue Znt3 transcription is 45-60% down-regulated in cortical regions of people with diagnosed Alzheimer's disease (Beyer et al 2009). This result is supported by the findings from Adlard et al who found a decline in the ZnT3 level of people suffering from Alzheimer's disease compared to controls (Adlard et al 2010).…”
Section: Znt3 and Alzheimer's Diseasementioning
confidence: 97%